Potential role of Hsp25 in calcium-modulated cardiomyocytes - Das, Tanuza; Yoo, Young Sook; Rhim, Hyewhon; Song, Eun Joo (WILEY, 2012)
Cardiac muscle contraction is initiated by the entry of Ca2+ ions from the extracellular spaces and the Ca2+ stores in the sarcoplasmic reticulum into the myoplasm. Calcium signaling is the most important factor in cardiac cell homeostasis. In this study, we investigated the effect of caffeine, an inducer of intracellular Ca2+ accumulation, on HL-1 cardiomyocytes by using a proteomic approach. Following the separation of the cell lysates and visualization of the protein spots using two-dimensional gel electrophoresis and silver staining, respectively, we identified 24 differentially expressed protein spots in the caffeine-treated group as compared with the controls by using MALDI-TOF/TOF MS. Of these 24 spots, 8 proteins were up-regulated and 16 proteins were down-regulated. These differentially expressed proteins are predominantly involved in cellular metabolism, cellular organization, and ion/protein transport. Furthermore, we found that Hsp25, one of the differentially expressed proteins, is modified by caffeine treatment. Depletion of Hsp25 transcripts by siRNA increased caffeine-mediated signaling, including ERK activation, and decreased the Ca2+ transient peak and expression of calsequestrin 2 in HL-1 cardiomyocytes. These results suggest that proteins having various functions are involved in the regulation of Ca2+ homeostasis, and that Hsp25 plays an important role in regulating cardiac function during caffeine response.
Keywords: HEAT-SHOCK PROTEINS; ATRIAL MYOCYTES; CAFFEINE; MICE; RAT; HEAT-SHOCK-PROTEIN-70; EXPRESSION; MUTATIONS; RECEPTORS; RELEASE